Evaluation of resistance to yam mosaic virus (YMV), genus Potyvirus in white yam (Dioscorea rotundata Poir.) - Odu, B.O.; Asiedu, Robert; Hughes, J.; Shoyinka, S.A.; Oladiran, O.A. (Elsevier, 2004)
Yam mosaic virus (YMV), genus Potyvirus; family Potyviridae is the most important virus infecting Dioscorea spp. in the tropics. It induces a variety of symptoms ranging from mild mosaic on leaves of infected plants to stunted growth. Field and laboratory studies were conducted in Nigeria to identify Dioscorea rotundata genotypes that are resistant to YMV. A total of 24 D. rotundata varieties were evaluated in the field under natural infection conditions at four locations in Nigeria during 1998 and 1999 planting seasons, and also in an insect-proof screenhouse using mechanical inoculation and vector transmission. The plants in the field were individually scored for virus symptom severity, while those in the screenhouse were indexed for YMV at 6, 8 and 10 weeks after inoculation by triple antibody sandwich enzyme-linked immunosorbent assay (TAS-ELISA). Analysis of the symptom severity scores showed highly significant differences (P<0.01) among the genotypes. Varieties TDr 1621, TDr 1640, TDr 35, TDr 2224 and TDr 93-48 were identified as resistant to field infection by yam viruses based on their low symptom severity scores (<2 on a 1–5 scale). In the screenhouse evaluation by mechanical and vector transmission only TDr 1621, TDr 1640, and TDr 93-48 remained free from YMV infection confirming resistance to YMV in these varieties.